TOWARDS GENDER EQUALITY: UKRAINE IN THE 21ST CENTURY - Tetyana V. Danylova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. This article attempts to examine the current state of addressing gender inequality in Ukraine. Methodology. The author has used methodology of historical inquiry, hermeneutical methodology and content analysis. Theoretical basis and results. Issues about gender imbalance are acute in Ukraine.  Gender inequality in politics is a matter of serious concern. Insignificant part of women in political and decision-making processes is a serious challenge to democracy. Discrimination in the labor market should be noted. Obvious gender inequality in the labor market has led to feminization of poverty. Violence against women has become an acute problem, which can be resolved at the state level only. Although international and national legislation is based on the principle of equality, in practice women are not equal in social life and activities. There is a deep contradiction between the new needs in society and the lack of conditions for their satisfaction. This situation appears to be a challenge to modern Ukrainian society and state of Ukraine, thus, immediate appropriate actions are required. Scientific novelty. It is essential to bring Ukrainian legislation into conformity with the constitutional principles of equality and European standards; develop appropriate and effective anti-discrimination norms and sanctions for violating gender legislation; introduce special measures to ensure gender parity in decision-making, in all public offices; conduct special information campaigns; develop and institutionalize gender studies and gender education at all stages; get more public control over the implementation of international commitments and principles of equal rights and opportunities for women and men. Conclusion. Appropriate mechanisms for overcoming gender stereotypes will contribute to integration of equal rights’ principle and opportunities.  Human resources policies require systematic approach to gender analysis and integration in order to address gender issues in program development. In the 21st century issues of gender equity should be a priority at all levels.